Psychological peculiarities of plagiarism and its correlation with creative abilities - Ульянова, Галина Олексіївна; Ульянова, Г. О.; Ульянова, Галина Алексеевна; Ulianova, Halyna O. (Springer Nature, 2017)
The relevance of the study is explained by the need for the development of effective mechanisms for preventing plagiarism. In this regard, it is important to clarify the nature of this phenomenon from a psychological point of view, as well as to study individual psychological peculiarities of a plagiarist’s personality in correlation with external factors, inducing types of behavior. The paper aims to analyze the psychological peculiarities of plagiarism as a violation of intellectual property rights and academic integrity, as well as to identify the relationship of proneness to plagiarism and creative abilities of an individual. The experiment involved 170 senior students and postgraduate students studying at National University “Odessa Law Academy”. There have been applied the author’s questionnaire on protection of intellectual property rights against plagiarism and the study of propensity to plagiarism in the process of writing scientific works; Ye. Tunic’s Questionnaire aimed at examining the level of personal creativity; H. Zivert’s “Definition of Creative Ability” test allowing to investigate the level of the ability to associate, visual creativity skills, ability to transform, variability of thinking, ingenuity. Student’s t-test was applied in order to examine the statistical differences. Psychological peculiarities of plagiarism involve the insufficient development of cognitive processes, lack of motivation, selfdistrust, and unawareness of negative consequences of plagiarism. It has been established that students and postgraduate students who have negative attitude to plagiarism and are not prone to it have a higher level of personal creativity and creative abilities as compared to those students who have experience of plagiarism and express readiness to use it, while these respondents are more prone to risk and resourceful, on the other hand, they are characterized by ready-made opinions and low level of freedom of associations.

Актуальність дослідження обумовлена необхідністю розроблення ефективних механізмів запобігання плагіату. У зв’язку з цим важливим є з’ясування сутності феномену плагіату з психологічної точки зору, дослідження індивідуально-психологічних особливостей особистості плагіатора у їх взаємозв’язку із зовнішніми чинниками, що спонукують до певного типу поведінки. Метою статті є аналіз психологічних особливостей плагіату як порушення прав інтелектуальної власності та академічної доброчесності, а також виявлення взаємозв’язку схильності до плагіату з творчими здібностями особистості. Визначено психологічні особливості плагіату та розкрито сутність криптомнезії у сфері творчої діяльності як психологічного прояву ненавмисного плагіату. Проаналізовано результати емпіричного дослідження взаємозв’язку схильності до плагіату та рівня розвитку творчих здібностей, зокрема особистісної креативності. Встановлено, що студенти та аспіранти, які негативно ставляться до плагіату та не мають до нього схильності, виявили більш високий загальний рівень розвитку особистісної креативності та творчих здібностей у порівнянні з тими, хто мав власний досвід плагіату та виявив готовність до його використання.
Ulianova H. Psychological peculiarities of plagiarism and its correlation with creative abilities / H. Ulianova // Science and Education. - Iss. 9. - Springer Nature, 2017. - P. 88-93.
Keywords: plagiarism; psychological peculiarities; creativity; creative abilities; плагіат; психологічні особливості; кріптомнезія; креативність; творчі здібності; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology